Transboundary Pollution, R&D Spillovers, Absorptive Capacity and International Trade - Dinar, Zeineb Aloui (International Journal of Economics and Financial Issues, 2014)
In this paper, we study the effects of absorptive capacity and R&D spillovers on cross-border pollution in a game played by two regulator-firm hierarchies. By means of a tax per-unit of pollution, a subsidy per-unit of original research and a subsidy per-unit of absorptive research, the regulators can reach the first-best outcome. We show that, in addition to free R&D spillovers and absorptive research, competition of firms on the common market help non-cooperating countries to better internalize transboundary pollution. More importantly, opening borders increase the per-unit emission-tax and decrease the per-unit original research subsidy. Thus, when the investment-cost parameters are sufficiently high, the international trade increases the original research, production. Consequently, the emission ratio is lower. Keywords: Transboundary pollution; R&D spillovers; absorptive capacity; international trade. JEL Classifications: D62; H21; O32.